2022
DOI: 10.1007/s10926-022-10056-5
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Injustice as a Determinant of the Severity of Post-traumatic Stress Symptoms Following Occupational Injury

Abstract: Background The present study assessed the role of perceived injustice in the experience and persistence of post-traumatic stress symptoms (PTSS) following work-related musculoskeletal injury. Methods The study sample consisted of 187 individuals who were absent from work as a result of a musculoskeletal injury. Participants completed measures of pain severity, perceived injustice, catastrophic thinking, post-traumatic stress symptoms, and disability on thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 83 publications
0
0
0
Order By: Relevance
“…PTSS can interfere with full participation in family, social, recreational, and occupational activities [21,63,64]. Avoidance is a central feature of the experience of PTSS where individuals are motivated to avoid situations or activities that might trigger memories of the trauma [18,20]. When trauma exposure has occurred in the workplace, the workplace might become a key object of avoidance and contribute to prolonged work absence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PTSS can interfere with full participation in family, social, recreational, and occupational activities [21,63,64]. Avoidance is a central feature of the experience of PTSS where individuals are motivated to avoid situations or activities that might trigger memories of the trauma [18,20]. When trauma exposure has occurred in the workplace, the workplace might become a key object of avoidance and contribute to prolonged work absence.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that across several high stress occupations, the prevalence and severity of PTSS is higher in women than in men [19]. For example, in a sample of health care professionals in emergency departments, Carmassi et al [20] observed significantly higher levels of PTSS in women than in men. In a recent study, Pavilanis et al [21] reported that women scored higher than men on a measure of PTSS following a workplace musculoskeletal injury.…”
Section: Introductionmentioning
confidence: 99%